Analysis of the metal adhesively bonded double cantilever beam specimen. (September 2015) - de Morais, A.B.
Abstract: The double cantilever beam specimen is currently standardized for measuring the mode I fracture energy of adhesive joints. In addition, it has been increasingly employed to evaluate the adhesive traction-separation law by the direct method, which involves crack tip separation measurements. The three-dimensional finite element analyses here conducted showed that significant anticlastic deformations of the metal adherends compromise the accuracy of the direct method in the elastic domain. It was also seen that the adherend plane stress and adhesive uni-axial strain hypotheses are adequate for the typical specimen geometries. Finally, the new elastic crack length correction derived from a beam model can be used to predict accurately the initial specimen compliance, to obtain conservative fracture energy values and to gain additional insight into the adhesive fracture behaviour.